2012 IEEE International Conference on Automation Science and Engineering (CASE) 2012
DOI: 10.1109/coase.2012.6386314
|View full text |Cite
|
Sign up to set email alerts
|

Partial Feedback Linearization Control of the three dimensional overhead crane

Abstract: Based on the partial feedback linearization, a novel nonlinear controller is analyzed and designed for three dimensional motion of overhead crane. Three control inputs composed of b ridge moving, trolley travelling, and cargo hoisting forces are used to drive five state variables consisted of bridge motion, trolley movement, cargo hoisting displacement, and two cargo swing angles. The control scheme is constituted by linearly combining two components: one is got from the nonlinear feedback of actuated states a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…The solution to track desired trajectory of trolley and anti-sway of load are particular characteristics of overhead crane. The approaches for anti-sway are based on PD techniques control [1], partial feedback linearization control [2,3], nonlinear control [4 -11], robustadaptive control [12 -14], fuzzy -neural network controller [15,16]. The above controllers are often used for uncertainly parameters of overhead crane and when executed to combine with two loop circuits : the adaptive parameters adjustment loop and control loop.…”
Section: Problem Statementmentioning
confidence: 99%
“…The solution to track desired trajectory of trolley and anti-sway of load are particular characteristics of overhead crane. The approaches for anti-sway are based on PD techniques control [1], partial feedback linearization control [2,3], nonlinear control [4 -11], robustadaptive control [12 -14], fuzzy -neural network controller [15,16]. The above controllers are often used for uncertainly parameters of overhead crane and when executed to combine with two loop circuits : the adaptive parameters adjustment loop and control loop.…”
Section: Problem Statementmentioning
confidence: 99%
“…Bechlioulis and Rovithakis [8] developed a multiple-input, multiple-output tracking controller with adaptive feedback linearisation and Shojaei et al [9] demonstrated the ability of adaptive feedback linearisation in aiding effective trajectory tracking in the presence of both parametric and nonparametric uncertainties in wheeled robots. Tuan et al [10] designed a controller based on partial feedback linearisation of the nonlinear dynamics of a 3D overhead crane.…”
Section: Shock and Vibrationmentioning
confidence: 99%
“…Fulfilling this gap, Park et al propose a feedback linearization for trolley and hoisting operations to guarantee asymptotic stability. Similarly, a partial feedback control is developed in [8]; the control is a linear combination of feedback linearization from actuated and unactuated dynamics. Subsequently, the closed-loop system is proven to be asymptotically stable.…”
Section: Introductionmentioning
confidence: 99%